2020
DOI: 10.1088/1757-899x/1006/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Traffic Congestion Impacts of Urban Road Network under Indian Condition

Abstract: Traffic congestion has been an area of major bother across the globe. The existing infrastructure is not able to cope with the new traffic demand. Furthermore the restriction of the space and outside activities influencing the traffic congestion. The emerging country like India, where the traffic conditions comprise heterogeneous traffic with no lane discipline, further creates more complicated scenarios for the researcher. A substantial portion of working hours is getting wasted on the roads because of traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 6 publications
0
14
0
2
Order By: Relevance
“…From 8 AM to 11 AM are considered as morning rush periods and from 2 PM to 3 PM are considered as morning offpeak hours. Video graphic survey was executed for the The researchers [16][17][18][19][20], though discussed about all congestion indices, but considered the buffer time index for the analysis. The BTI has been considered as congestion index in the current study.…”
Section: Choice Of Road Networkmentioning
confidence: 99%
“…From 8 AM to 11 AM are considered as morning rush periods and from 2 PM to 3 PM are considered as morning offpeak hours. Video graphic survey was executed for the The researchers [16][17][18][19][20], though discussed about all congestion indices, but considered the buffer time index for the analysis. The BTI has been considered as congestion index in the current study.…”
Section: Choice Of Road Networkmentioning
confidence: 99%
“…Traffic congestion significantly impacts residents, such as wasting fuel, wasting time for nothing, and causing environmental damage due to air pollution emitted by motorized vehicles [18], [26]- [28]. This waste causes costs that should be used or allocated by the community for other uses to be spent on transportation costs such as fuel consumption.…”
Section: Capacity (C) and Density (D)mentioning
confidence: 99%
“…They concluded that the travel time-based measure gives noticeable results about congestion. Samal et al [9] studied the traffic congestion on the urban arterial in India using the travel time reliability measures. They found that the users were wasting 50 % of the time in the congestion.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in congestion level leads to the extra delay to the road users and the personage tension and high amount of emissions [8][9][10]. Traffic in developing countries such as India, Taiwan and Vietnam is highly heterogeneous in nature, characterized by a broad mix of vehicles with diverse static and dynamic features in the absence of a lane discipline.…”
Section: Introductionmentioning
confidence: 99%